SCHOOL MONITORING - FOLLOW UP (CIPEEX, 2024)
THE "SCHOOL MONITORING" SOFTWARE IS AN INNOVATIVE PROPOSAL THAT AIMS TO MONITOR THE STUDENT'SSCHOOL BEHAVIOR. IT OFFERS FACILITIES SUCH AS VIEWING GRADES AND A REAL-TIME CHAT FOR PARENTS ORGUARDIANS TO CONTACT EDUCATORS AT ANY TIME. THIS WORK INVOLVED RESEARCH AND INTERVIEWS WITHPARENTS AND EDUCATORS, AS WELL AS A PRESENTATION AT SINACEN OF THE UNIVERSITY CENTER OFANÁPOLIS.THE MAIN OBJECTIVE IS TO ALLOW PARENTS OR GUARDIANS TO BE MORE AWARE OF THEIR CHILDREN'SBEHAVIOR AT SCHOOL, FACILITATING THE MAKING OF APPROPRIATE DECISIONS. THE "SCHOOL MONITORING"ALSO AIMS TO BRING PARENTS AND EDUCATORS CLOSER TOGETHER AND INFORM PARENTS ABOUT THEDIFFICULTIES THEIR CHILDREN MAY ENCOUNTER IN SCHOOL LIFE.FOR THE DEVELOPMENT OF THE APPLICATION, WE USED A USER-CENTERED APPROACH, CONDUCTINGRESEARCH WITH PARENTS AND EDUCATORS TO UNDERSTAND THEIR NEEDS AND CHALLENGES. BASED ONTHIS INFORMATION, WE CREATED A SET OF REQUIREMENTS AND FUNCTIONALITIES. WE CHOSE THE AGILESCRUM METHODOLOGY AND HELD MEETINGS WITH THE TEAM TO DECIDE ON THE BEST FEATURES FOR THEAPPLICATION'S MVP.DESPITE THE EXISTENCE OF SIMILAR APPLICATIONS ON THE MARKET, OUR PROPOSAL BRINGS ANINNOVATION: IT ALLOWS PARENTS OR GUARDIANS TO BE AWARE OF THEIR CHILD'S BEHAVIOR AND DIFFICULTIES,ENABLING THEM TO TAKE THE BEST MEASURE TO SOLVE THESE SITUATIONS. THE INTERVIEWS MADE ITCLEAR THAT OUR AUDIENCE WANTS TO KNOW RECURRENTLY HOW THEIR CHILD IS BEHAVING AT SCHOOL AND IFTHEY ARE FACING ANY DIFFICULTY, EITHER IN ACTIVITIES OR IN RELATION TO OTHER COLLEAGUES.